Mathematical approach for understanding deagglomeration behaviour of drug powder in formulations with coarse carrier - Irene Parisini; James L. Collett; Darragh Murnane (Elsevier, 2015)
Deagglomeration of cohesive particles in combination with coarse carrier is a key requirement for inhaled formulations. The aim of the project was to propose a mathematical approach to understand aerosolization behaviour of micronized particles alone and in formulation with carriers. Salbutamol sulphate and salmeterol xinafoate were blended separately with fine lactose (ratio 1:4) and fine and coarse lactose (1:4:63.5). Laser diffraction was employed to characterize the powder median particle size. The deagglomeration of micronized materials followed an asymptotic monoexponential relationship. When the coarse lactose was added, the relationship fitted a bi-exponential equation showing an easily and a poorly dispersed fraction. Using model hydrophobic and hydrophilic APIs, this study has demonstrated the utility of an analytical approach that can parameterize deagglomeration behaviour of carrier-free and carrier-based inhalation formulations. The analytical approach provides the ability to systematically study the effect of material, formulation and processing factors on deagglomeration behaviour.